Breaking the limits of experimental pancreas transplantation: Working toward the clinical ideal graft - Ferrer-Fàbrega, Joana; Folch-Puy, Emma; Llaves-López, Andrea; García-Pérez, Rocío; Fuster, Josep (Frontiers in Transplantation, 2022)
Pancreas transplantation is, at present, the only curative treatment for type-1 diabetes that maintains normoglycemia thus avoiding complications arising from poor glycemic control. Despite its great benefits, the number of pancreas transplants has decreased significantly since its inception in the late 1960s, largely due to demographic changes and the consequent suboptimal quality of donors. The selection criteria for pancreas donors mainly depend on morphological variables such as fatty infiltration, fibrosis, or edema, as well as both functional (amylase and lipase) and clinical variables of the donor. However, the final criterion in the decision-making process is the somewhat subjective assessment of a trained surgeon. That being said, the recent incorporation of graft perfusion machines into clinical practice seems to be changing the work dynamics of the donor organ retrieval team, facilitating decision-making based on objective morphological and functional criteria. Normothermic perfusion using perfusate with supplemental oxygen replicates near physiological parameters thus being a promising strategy for organ preservation. Nevertheless, optimum perfusion parameters are difficult to establish in pancreas transplantation given its complex vascular anatomy combined with an intrinsically low blood flow. The objective of this work is to analyze the results published in the recent literature relating to the considerations of ex-vivo normothermic graft perfusion machines and their usefulness in the field of pancreas transplantation.